Updates on Aldose Reductase Inhibitors for Management of Diabetic Complications and Non-diabetic Diseases - Singh Grewal, Ajmer; Bhardwaj, Shashikant; Pandita, Deepti; Lather, Viney; Singh Sekhon, Bhupinder (Mini Reviews in Medicinal Chemistry, 2016)
Diabetes mellitus occurrence has been associated to the modification of the physiological levels of glucose and is often accompanied by several long-term complications, namely neuropathy, nephropathy, retinopathy, cataract, and cardiovascular. Aldose reductase (AR) is an enzyme of aldoketo reductase super-family that catalyzes the conversion of glucose to sorbitol in the polyol pathway of glucose metabolism. In this context, aldose reductase inhibitors (ARIs) have received much attention worldwide. Decreased sorbitol flux through polyol pathway by ARIs could be an emerging target for the management of major complications of diabetes. The present review article describes a brief overview of the role of aldose reductase in the diabetic complications, advances achieved on ARIs and their potential use in the treatment and management of the major diabetic complications such as cataract, retinopathy, neuropathy, nephropathy and cardiovascular. The ARIs developed vary structurally, and representative structural classes of ARIs include i) carboxylic acid derivatives (such as Epalrestat, Alrestatin, Zopalrestat, Zenarestat, Ponalrestat, Lidorestat, and Tolrestat), ii) spirohydantoins and related cyclic amides (such as Sorbinil, Minalrestat, and Fidarestat), and iii) phenolic derivatives (related to Benzopyran-4-one and Chalcone). Among these inhibitors, Epalrestat is the only commercially available inhibitor till date. In addition, some other ARIs such as Sorbinil and Ranirestat had been advanced into late stage of clinical trials and found to be safe for human use. The role of various natural ARIs in management of diabetic complications will be discussed. Adapting ARIs could prevent sepsis complications, prevent angiogenesis, ameliorate mild or asymptomatic diabetic cardiovascular autonomic neuropathy and appear to be a promising strategy for the treatment of endotoxemia and other ROS-induced inflammatory diseases. The role of ARIs in non-diabetic diseases will also be discussed.
Keywords: Sepsis complications